IMPLEMENTASI RELAKSASI GENGGAM JARI DALAM MENURUNKAN NYERI AKUT PADA PASIEN DENGAN HEMOROID - Dea Oktaria Nur; Suci Khasanah (Sekolah Tinggi Pariwisata Mataram, 2022)
Background: Hemorrhoids, hemorrhoids or more commonly known as hemorrhoids are dilated veins in the anal area originating from the hemorrhoidal plexus. Pain is one of the symptoms of hemorrhoidal patients due to inflammation and edema caused by thrombosis. The combination of pharmacological and non-pharmacological treatment is the best way to control pain. One of the non-pharmacological techniques used is the finger grip relaxation technique. Methods: This study used a descriptive design in the form of a case study approach to nursing practice. The case study in this study examined acute pain in hemorrhoidal patients after the finger grip relaxation technique was effective for 3 x 2 4 hours. Results: The results showed that the patient's pain scale before implementation was 6, besides that the patient also showed symptoms of grimacing in pain, BP: 167/94 mmHg, N: 95 x/minute and RR: 26 x/minute. After being given implementation for 3x24 hours, it was seen that there was a decrease in the patient's pain scale to 3, besides that the patient also showed symptoms of being calmer, BP: 140/85 mmHg, N: 84 x/minute and RR: 20 x/minute. Conclusion: Nursing actions by performing finger grip relaxation techniques can reduce acute pain in patients where there is a decrease in the pain scale by 3.